(untitled) (Revista Española de Derecho Internacional, 2007)
Article 12 of the United Nations Convention on Jurisdictional Immunities of States and their Property regulates an exception to the jurisdictional immunity that includes the «personal injuries and damage to property» committed by a foreign State in the territory of the State of the forum, in accordance with the territoriality principle, without making its application conditional on the distinction between iure gestionis and iure imperii acts, in spite of the fact that in this second case the practice does not always confirm the acknowledgement of the mentioned jurisdictional immunity. Furthermore, article 12 is not applicable to armed conflict situations, since for those, the State practice still preserves the jurisdictional immunity. On the other hand, the practice review does not support the existence of an exception to the jurisdictional immunity in cases to which universal civil jurisdiction applies to serious human rights violations attributed to the foreign State. In the universal field, it seems highly improbable that a majority of States will accept an exception to a jurisdictional immunity of such characteristics, without disregarding the conventional development in the European regional field that might be adopted in the framework of the human rights protection system constituted under the 1950 Rome Convention.